1955
DOI: 10.1002/jlac.19555940304
|View full text |Cite
|
Sign up to set email alerts
|

Über einige weitere Umsetzungen des Ω‐Nitroacetophenons Über aliphatische Nitroverbindungen XII

Abstract: 191 Anilino-isonitrosoacetophenon. Entsteht analog aus Bromisonitrosoacetophenon und Anilin. Aus Toluol erhiilt man das Produkt in Form gelblicher Bliittchen. Leicht loslich in Alkohol, Ather, Chloroform, Benzol. Schwer loslich in Ligroin. Schmp. 147 O. Die Verbindung ist identisch mit der aus Chlorisonitrosoacetophenon zu erhaltenen21). Schmp. und Mischschmp. 147 0. Aminomethyl-phen yl-carbinol. 1,83 g Chlorisonitrosoacetophenon werden in 100 ccm abs. Ather gelost. Dann liilt man unter mechanischem Riihren 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1960
1960
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Dornow et al later reported high-yielding nitro-Mannich reactions of nitroacetophenone and nitroacetone with a variety of methanolamines formed from secondary amines and formaldehyde (Scheme ). , They also demonstrated that nitroacetophenone and nitroacetone react with preformed aryl imines in the presence of acetic anhydride. By refluxing the reaction mixture elimination of the alkylacetamide occurred to form nitroalkenes 42 in low to good yields.…”
Section: Early Developmentsmentioning
confidence: 99%
“…Dornow et al later reported high-yielding nitro-Mannich reactions of nitroacetophenone and nitroacetone with a variety of methanolamines formed from secondary amines and formaldehyde (Scheme ). , They also demonstrated that nitroacetophenone and nitroacetone react with preformed aryl imines in the presence of acetic anhydride. By refluxing the reaction mixture elimination of the alkylacetamide occurred to form nitroalkenes 42 in low to good yields.…”
Section: Early Developmentsmentioning
confidence: 99%
“…Some of the active hydrogen materials which have been added to N-benzylideneanilines are: acetoacetic esters and benzoylacetic esters (235), diethyl malonate (174, 235, 278), methyl ethyl ketone (the methyl group adds rather than the methylene) (174), 2methylbenzopyrrole (active hydrogen is in the 3-position) (203), benzopyrrole (adds in the 3-position) (202), antipyrine (204), -cyanoethyl acetate, ethylmalonamide, malonamide (161), methyl ketones with boron trifluoride etherate in equimolar amounts (methylene ketones do not react under these conditions) (248), Kojic acid (adds in the 6-position) ( 14), 2-methylquinoline methyl iodide (139), methyl nitrite, diethylamine favors the addition of ethyl and propyl nitrites (163), isopropyl nitrite fails to react (125), benzyl nitrite adds very easily in the presence of diethylamine (63), -nitroethyl acetate (65), 8-hydroxy quinoline (adds in the 7-position) (210), -phenylethyl acetate with an aluminum chloride catalyst (155), benzyl sodium sulfonate with phenyllithium (172), acetophenone with an amine hydrochloride catalyst (149), the sodium salt of phenylacetic acid in sodamide (253), the ethyl ester of phenylacetic acid (155), acetic anhydride (mono product) (4), a-and /3-naphthol (22), nitroacetonitrile (230), ethylnitroacetic acid (65, 66) and -nitroacetophenone (69). N-Benzylidene-o-carboxyaniline exists as an equilibrium of the imine and the cyclic addition product (249).…”
Section: C=chmentioning
confidence: 99%
“…For example, it has been reported that acetylene adds to N-butylidene-tbutylamine in the presence of cuprous chloride at 45' in dioxane to give 3-t-butylaminohexyne-3 (177). (253), the ethyl ester of phenylacetic acid (155), acetic anhydride (mono product) (4), a-and @naphthol (22), nitroacetonitrile (230), ethylnitroacetic acid (65,66) and w-nitroacetophenone (69). N-Benzylidene-o-carboxyaniline exists as an equilibrium of the imine and the cyclic addition product (249).…”
mentioning
confidence: 99%
“…An old paper by Dornow and coworkers [126] described the synthesis of α‐nitrochalcone by reacting α‐NO 2 ‐acetophenone with a Schiff base that was pre‐prepared from benzaldehyde. The reaction was performed in diethyl ether in the presence of acetic anhydride (Ac 2 O) (reaction 1, Figure 30).…”
Section: Different α‐Substituted Chalconesmentioning
confidence: 99%